Quizziz sebagai Alat Penilaian Teks Eksplanasi pada Peserta Didik di Kelas VIII B SMPN 2 Semarang - Indah Fitrianingrum; Tri Wahyuni; Hesti Ambarwati; Asep Purwo Yudi Utomo; Eva Wulandari; Rossi Galih Kesuma; Titin Prihartini (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Learning is an activity that results in a change from those who do not know to know, from those who are unable to become capable. While learning refers to two concepts, namely learning and teaching. When the learning process takes place there will definitely be students who are not interested in the learning material delivered by the teacher. To overcome this, teachers must make innovations and updates in learning so that students can get motivation to learn and a pleasant learning atmosphere so that it is easier to accept material. Technology in the world of education is a learning system that supports learning so that learning becomes fun and achieves the desired results. Many learning platforms on the internet can be accessed for free, one of which is Quizziz. Quizizz is a platform for creating an interactive quiz game that can be used in class or outside the classroom in the form of homework. The method used in this research is descriptive qualitative with class VIII B students at SMPN 2 Semarang as the subject. Data collection techniques used are observation and documentation. The data analysis technique that the researcher used included three stages, namely data reduction, data presentation, and concluding data. The results that the researchers got from the application of Quizziz as an explanatory text assessment tool for class VIII B students at SMPN 2 Semarang. interactive quiz media on explanatory text material at SMPN 2 Semarang shows that the use of the Quizziz application is beneficial for teachers and students even though there are still drawbacks.